Концепция проектирования компактных наземных пусковых устройств для запуска беспилотных летательных аппаратов - Середа, Владислав Александрович (НТУ "ХПИ", 2016)
Сформулирована проблематика ввода в полет с поверхности беспилотного летательного аппарата за счет внешней энергетики. Записана полезная функция, а также общие и частные управляющие параметры наземных пусковых устройств (НПУ). Приведены кинематические схемы НПУ различного типа, полученные в результате модернизации. Описана лежащая в основе метода оптимизации длины направляющей комплексно-сопряженная модель катапульт. Изложен принцип параметрического поиска закона распределения тягового усилия путем нормирования работы расширения в определенном интервале.

The problems of launching an unmanned aerial vehicle (UAV) from the surface using external energy are formulated. The general shortcoming of modern ground launching devices (GLD) is a significant length of the UAV acceleration. Using intensive methods for improving dynamic performance of GLDs is ineffective. The goal is to develop the methods of optimization of dynamic characteristics of GLDs. To this end a useful function, as well as general and specific control parameters of ground catapults are derived. Cinematic schemes for GLD of different types, obtained by modernizing the timing drive or transmission gear ratio are presented. We describe the complex conjugate model of pneumatic catapult underlying the optimization method family. The principle of parametric determination of the law of distribution of traction by normalizing the expansion work in a certain range is discussed. The software for implementing the optimization algorithm using machine methods is proposed. The capacities of the design tools are presented in the form of a phase cut of a pneumatic GLD calculation domain. The comparative analysis of the results of optimization of different types of catapults obtained by modernizing their transmission or drive is carried out.
The concept of designing compact ground launching devices for launching unmanned aerial vehicles
Keywords: полезная функция; параметрическая оптимизация; характеристический критерий; управляемые параметры; комплексная модель; useful function; parameter optimization